Differential expression of specific cellular defense proteins in rat hypothalamus under simulated microgravity induced conditions: Comparative proteomics. Issue 11 (29th April 2014) - Iqbal, Javed; Li, Wang; Hasan, Murtaza; Liu, Kefu; Awan, Umer; Saeed, Yasmeen; Zhang, Yongqian; Muhammad Khan, Arif; Shah, Amin; Qing, Hong; Deng, Yulin
<x xml:space="preserve">Abstract</x> Microgravity severely halts the structural and functional cerebral capacity of astronauts especially affecting their brains due to the stress produced by cephalic fluid shift. We employed a rat tail suspension model to substantiate simulated microgravity (SM) in brain. In this study, comparative mass spectrometry was applied in order to demonstrate the differential expression of 17 specific cellular defense proteins. Gamma‐enolase, peptidyl‐prolyl cis‐trans isomerase A, glial fibrillary acidic protein, heat shock protein HSP 90‐alpha, 10 kDa heat shock protein, mitochondrial, heat shock cognate 71 kDa protein, superoxide dismutase 1 and dihydropyrimidinase‐related protein 2 were found to be upregulated by HPLC/ESI‐TOF. Furthermore, five differentially expressed proteins including 60 kDa heat shock protein, mitochondrial, heat shock protein HSP 90‐beta, peroxiredoxin‐2, stress‐induced‐phosphoprotein, and UCHL‐1 were found to be upregulated by HPLC/ESI‐Q‐TOF MS. In addition, downregulated proteins include cytochrome C, superoxide dismutase 2, somatic, and excitatory amino acid transporter 1 and protein DJ‐1. Validity of MS results was successfully performed by Western blot analysis of DJ‐1 protein. This study will not only help to understand the neurochemical responses produced under microgravity but also will give future direction to cure the proteomic losses and their after effects in astronauts.